Autonomous Motivation as a Mediator Between an Empowering Climate and Enjoyment in Male Volleyball Players - Sofia Mosqueda; Jeanette M. López-Walle; Pablo Gutiérrez-García; Juan García-Verazaluce; José Tristán (MDPI AG, 2019)
The objective of this work was to analyze a mediation model concerning the perception of an empowering climate generated by a coach and enjoyment through the autonomous motivation of athletes. The sample consisted of 71 elite male volleyball players from six countries. The age range was 14 to 18 years (M = 16.5, SD = 0.96). The relationships between the perception of an empowering climate, autonomous motivation, and enjoyment were positive and significant. The mediation model showed that autonomous motivation acts as a mediator in the relationship between the perception of an empowering climate generated by the coach and the enjoyment reported by the athletes.